G472 Are any of the admissions for term infants for primary management of jaundice avoidable?. (24th May 2017) - Battersby, C; Michaelides, S; Upton, M; Rennie, J
Abstract : Aims: To determine the proportion of term babies admitted for jaundice to English neonatal units in England 2011–13 which can be appropriately cared for in a setting where mother and baby are kept together; to identify risk factors for admission for the management of jaundice. Methods: We conducted a restrospective observational study using admissions data 2011–13 from all 163 neonatal units in England held in the National Neonatal Research Database (NNRD) and live births in England data from the Office for National Statistics (ONS). Measures included number and proportion of term live births admitted for the primary reason of jaundice, patient characteristics, postnatal age at admission, total length of stay, phototherapy, intravenous fluids, exchange transfusion and kernicterus. Results: Jaundice was the fourth most common reason for admission from within the hospital (6950/128 788, 5%) but the most common primary reason for admision from home (1082/4 858, 22%). Term babies admitted for jaundice were more likely to be male, born at 37 weeks gestation, of Asian ethnicity or one of a multiple birth. The majority of babies required only a brief period of phototherapy with only 30% requiring intravenous fluids, suggesting that the majority could be appropriately managed in a transtional care setting, avoiding separation of mother and baby. Admission from home was significantly later (3.9 days) compared with those admitted from within the hospital (1.7 days), and although numbers were small, the rate of kernicterus was almost five times higher among those admitted from home versus hospital. Conclusion: Around a third of infants admitted to neonatal care primarily for jaundice management may be appropriately cared for in a transitional setting avoiding separation of mother and baby. Infants at risk of jaundice in the community may benefit from an additional postnatal visit around the third day of life to allow for early identification and referral for jaundice management. Further work is needed to understand variation in facilities and definitions of transitional care, referral pathways between primary and secondary care, and community postnatal care provision.